2013
DOI: 10.1503/cmaj.121274
|View full text |Cite
|
Sign up to set email alerts
|

Just ask: discussing goals of care with patients in hospital with serious illness

Abstract: CMAJ, April 1, 2014, 186(6) 425 O ur population is aging, and older patients are living longer with chronic illness. Technology-laden end-of-life care is associated with poorer quality of life, lower satisfaction with care and increased anxiety and depression for family members.1 Ad vance care planning can increase the quality of life of dying patients, improve the experience of family members and decrease health care costs. 1-3Advance care planning is a process by which patients consider options for future … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
1
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(94 citation statements)
references
References 54 publications
1
86
1
6
Order By: Relevance
“…19 Our results build on that work by providing further direction on which specific elements should be discussed with patients and families in hospital. For example, both patients and family members rated prognostic disclosure as highly important.…”
Section: Discussionsupporting
confidence: 69%
“…19 Our results build on that work by providing further direction on which specific elements should be discussed with patients and families in hospital. For example, both patients and family members rated prognostic disclosure as highly important.…”
Section: Discussionsupporting
confidence: 69%
“…This will help to build a therapeutic relationship with the patient [30]. These opportunities/triggers can be: the presence of cor pulmonale [22]; the need for ventilation in the previous year [22]; arterial partial pressure of carbon dioxide >45 mmHg or FEV1 <30% [22]; recent hospital admission or consultation [26,30,39,50]; oxygen dependency or weight loss [22]; observed deterioration in the patient's condition [22,30,39,50]; age above 70 years [18,22]; assessment of therapy options [30,50].…”
Section: Improving Palliative Care Communicationmentioning
confidence: 99%
“…Any disagreements identified should be negotiated with the patient, to come to a shared decision [24,50,55]. [37] Lack of time in appointments to discuss all topics [18,37] Discussions may take away patients' hope [37] Lack of feedback and documentation [18,30,40,45] Lack of thorough knowledge of the patient [3,18] Difficulty to start conversations and to choose the right time [3,18,22,26,30,39,40,44,45] Difficulty for patients to understand and accept information in short periods of time [3,29,52] Vision of palliative care as confined to the last days of life and exclusive of life sustaining treatments [29,30] Uncertainty to prognose in COPD [5,18,22,39,40,45] Reluctance of palliative care services to care for patients with COPD [29] Complex discharge planning for COPD patients [18] Facilitators Patients who had relatives or friends who had died recently [37] Patients' trust in their physician [37] Patients interpret physicians' skills as very good [37] Patients' belief that physicians truly care about the patient [37] Good patient-physician relationship [29,37] Physicians who cared for many...…”
Section: Improving Palliative Care Communicationmentioning
confidence: 99%
“…It has previously been shown that when physicians address end-of-life issues with patients, there is subsequently a greater likelihood that the patient's preferences will be respected, and there are lower levels of anxiety, stress and depression among the family (33). To this end, it is essential for the patient and family to be able to come together to deliberate at a quiet time, when emotions are not running high, and outside the context of acute events, and together with the intensivist, so that this latter may explain the therapeutic options available in case of organ failure, and also so that the patient and family may communicate their preferences for such a situation (46). Explaining what can be done implicitly suggests what will not be done.…”
Section: The Intensivist As An Outside Consultant To Guide Informed Dmentioning
confidence: 99%